Determination of Natural Radioactivity in Soil Samples around Gold Mining Area in Khamkeut District, Bolikhamxay Province,Laos Using Gamma Ray Spectrometer with NaI (Tl) Detector - Leuangtakoun, Somsavath (H. : ĐHQGHN, 2018)
This paper presented the method of determining the radioactivity of 40K, 226Ra and 232Th in soil samples by gamma-ray spectrometer using NaI (Tl) scintillation detector. The radioactivity of each isotope is calculated based on the net count rate in the energy window characteristic for the 40K, 226Ra and 232Th radioisotopes respectively. We have determined activity concentrations of the natural radionuclides 226Ra,232Th and 40K in 15 soil samples collected around gold mines of Khamkeut district, Bolikhamxay Province, Laos. The average activity concentrations of the natural radionuclides 226Ra, 232Th and 40K are 46.58 ± 7.36 , 71.19 ± 5.42 and 574.62 ± 25.02 Bq.kg-1, respectively. The average activity concentrations of 226Ra and 232Th in this work are higher than those of Bolikhamxay Province, Laos and the world average values. The estimated average outdoor annual effective dose (E) and radium equivalent actitvity (Raeq) are 0.10 ± 0.004 mSv.yr-1 and 192.64 ± 16.12 Bq.kg-1, respectively.